2010
DOI: 10.1598/rrq.45.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Ease of Implementation of an Academic Vocabulary Intervention for Linguistically Diverse Students in Urban Middle Schools

Abstract: The present study aims to advance the extant research base by evaluating the implementation and effectiveness of an academic vocabulary program designed for use in mainstream middle school classrooms with high proportions of language minority learners. The quasi‐experimental, mixed‐methods study was conducted in 21 classes (13 treatment matched to 8 control) in seven middle schools in a large district, with 476 sixth‐grade students (346 language minority learners, 130 native English speakers). Classroom observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
288
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(307 citation statements)
references
References 64 publications
11
288
0
4
Order By: Relevance
“…In their study on the effectiveness of an after-school program for Spanish-speaking middle school LEP students, Townsend and Collins (2009) showed that a well-designed research-based intervention can be beneficial for enhancing academic vocabulary knowledge of language minority students. In other studies (August et al, 2009;Lesaux et al, 2010;Proctor et al, 2011), researchers found that the effects of their treatment did not differ according to the language minority status of the students. Both EO and language minority students benefitted equally from the intervention.…”
Section: Importance Of Academic Vocabulary Knowledgementioning
confidence: 88%
See 1 more Smart Citation
“…In their study on the effectiveness of an after-school program for Spanish-speaking middle school LEP students, Townsend and Collins (2009) showed that a well-designed research-based intervention can be beneficial for enhancing academic vocabulary knowledge of language minority students. In other studies (August et al, 2009;Lesaux et al, 2010;Proctor et al, 2011), researchers found that the effects of their treatment did not differ according to the language minority status of the students. Both EO and language minority students benefitted equally from the intervention.…”
Section: Importance Of Academic Vocabulary Knowledgementioning
confidence: 88%
“…Though various intervention studies have shown success in supporting students to learn academic words, only a handful have demonstrated effectiveness for language minority students in the middle grades (Carlo et al, 2004;Snow, Lawrence, & White, 2009;Proctor et al, 2001;Lawrence et al, 2012;August, Branum-Martin, Cardenas-Hagan, & Francis, 2009;Lesaux, Kieffer, Faller, & Kelley, 2010;Townsend & Collins, 2009;Vaughn et al, 2009). In their study on the effectiveness of an after-school program for Spanish-speaking middle school LEP students, Townsend and Collins (2009) showed that a well-designed research-based intervention can be beneficial for enhancing academic vocabulary knowledge of language minority students.…”
Section: Importance Of Academic Vocabulary Knowledgementioning
confidence: 99%
“…Otras actividades requerían que los estudiantes clasificaran las palabras según su familia semántica o sus afijos, solicitando igualmente que analizaran los morfemas de las palabras (es decir, raíz y afijos) en relación tanto a la creación de significado como al análisis estructural. Todas las actividades incorporaban métodos que se han mostrado eficaces en el aprendizaje de idiomas, tales como el uso de elementos visuales y de visualización; estrategias de aprendizaje de palabras; juegos de rol con palabras; la escritura de oraciones e historias incorporando las palabras; ejercicios de rellenar huecos con palabras; la creación de un muro de palabras; requerir a los participantes que desarrollen y mantengan tarjetas con palabras o un cuaderno con un diccionario del vocabulario; juegos de palabras; y la revisión explícita de vocabulario clave al final de cada lección (Beck et al 2002, Graves 2006Lesaux et al 2010b). Por último, las tareas asignadas se centraron en la promoción de la conciencia léxica, solicitando a los estudiantes que identificaran las palabras objeto de estudio fuera del aula (por ejemplo, en casa, en el periódico o en la televisión).…”
Section: Programa De Enriquecimiento Del Vocabulariounclassified
“…We suggest Lesaux et al's (2010) quasi-experimental study of the effectiveness of an academic vocabulary program in multilingual, urban middle-schools be replicated to find out if the positive results hold in different language learning contexts. The original study is described in sufficient detail to allow for replication.…”
Section: The Original Studymentioning
confidence: 99%
“…The replications conducted in varied settings will not only test the effectiveness of the original framework but also indicate which aspects of the original intervention will need to be modified for a particular context. Indeed, the research reported in Lesaux et al (2010) has been cited to develop the justification for using similar vocabulary teaching with vastly different populations. For instance, Tighe & Schatschneider (2015) leverage the Lesaux et al research to make the case for fostering morphological awareness as a predictor of adult reading comprehension abilities, despite the fact that this work was carried out largely with children.…”
Section: Approaches For Replicationmentioning
confidence: 99%